LECTURES ON DEMAND IN ALN: ENHANCING THE ONLINE LEARNING EXPERIENCE - Latchman, H. A.; Latchman, Sheryl M. (Online Learning, 2001)
It is now well known that asynchronous learning networks (ALNs) provide effective mechanisms for facilitating interaction within learning communities in which the learners are separated by distance or time constraints. However, despite the infrastructure and tools which make ALNs so successful, questions have been raised about the time and effort required on the part of instructors to generate effective ALN course materials. In this paper we address these and other concerns in the use of ALN and propose the use of a “Lectures-on-Demand” methodology to allow ALN students access to the actual classroom experience. The Lectures-on-Demand method incorporates the spoken word, spontaneously written material and other facets of natural human communication into the ALN infrastructure. This approach allows students to ‘attend’ regular classes in real time via the Internet, as well as to have asynchronous access to digitally stored video material with hyperlinks to online training resources at any time. The paper discusses the technical requirements from the user and provider perspectives and describes ongoing efforts at the University of Florida where an online MS degree in Electrical Engineering is now being offered using the Lectures on Demand approach and online courses toward a BS in Electrical Engineering are presently being developed with the same tools.